Great Wall of Lucy Wu - Shang, Wendy Wan Long (New York Scholastic Press, 2011)
Eleven-year-old aspiring basketball star and interior designer Lucy Wu is excited about finally having her own bedroom, until she learns that her great-aunt is coming to visit and Lucy will have to share a room with her for several months, shattering her plans for a perfect sixth-grade year.
700L
97715
Keywords: Individuality; Family life; Chinese Americans; Great-aunts; Schools